Surgical Lip Remodeling Following Permanent Filler Injection: A Scoping Review. Issue 2 (13th March 2022) - Rauso, Raffaele; Fragola, Romolo; Fasano, Morena; Zerbinati, Nicola; Nicoletti, Giovanni Francesco; Lo Giudice, Giorgio
Abstract : Abstract: Over the years, several techniques have been introduced to obtain permanent lip enhancement, such as the use of silicone lip implants or the off-label use of permanent fillers. Although some reports indicate that permanent lip filler is safe, many others describe early- and late-onset complications. The main issue with permanent lip fillers is the lack of a standard technique to correct undesirable results. The aim of this scoping review was to list and evaluate the surgical pathways described in literature to correct lip deformity resulted from the injection of permanent fillers. The methods and the inclusion criteria of this work were specified in advance and documented in a protocol, according to the PRISMA 2009 checklist. The research was carried out on electronic databases PubMed, Cochrane Library, and Scopus databases identifying articles from March 1991 to December 2020 and conducted up to December 23rd, 2020. Articles language was limited to English. The selection process identified 3 retrospective studies eligible for inclusion. 73 patients and a total of 111 lips (72 upper and 39 lower) were considered. Two early complications were identified, 1 suture dehiscence and 1 total lip mucosa necrosis. Surgical lip remodeling following permanent filler injection seems to be an effective approach although the surgical pathway needs to be customized per each patient. Complication rate seems to be coherent to lip surgery performed with reconstructive purposes. To confirm these data case-control studies with much wider cohorts are needed to reach statistical significance.